Impact of Erythromycin as a Prokinetic on the Gut Microbiome in Children with Feeding Intolerance-A Pilot Study - Aravind Thavamani; Senthilkumar Sankararaman; Hilmi Al-Shakhshir; Mauricio Retuerto; Sujithra Velayuthan; Thomas J. Sferra; Mahmoud Ghannoum (MDPI AG, 2023)
Background: Studies have demonstrated that the gut microbiome changes upon exposure to systemic antibiotics. There is a paucity of literature regarding impact on the gut microbiome by long-term usage of erythromycin ethyl succinate (EES) when utilized as a prokinetic. Methods: Stool samples from pediatric patients with feeding intolerance who received EES (N = 8) as a prokinetic were analyzed for both bacteriome and mycobiome. Age-matched children with similar clinical characteristics but without EES therapy were included as controls (N = 20). Results: In both groups, Proteobacteria, Firmicutes, and Bacteroidetes were the most abundant bacterial phyla. Ascomycota was the most abundant fungal phyla, followed by Basidiomycota. There were no significant differences in richness between the groups for both bacterial and fungal microbiome. Alpha diversity (at genus and species levels) and beta diversity (at the genus level) were not significantly different between the groups for both bacterial and fungal microbiome. At the species level, there was a significant difference between the groups for fungal microbiota, with a p-value of 0.029. We also noted that many fungal microorganisms had significantly higher p-values in the EES group than controls at both genera and species levels. Conclusions: In this observational case-control study, the prokinetic use of EES was associated with changes in beta diversity between the groups for mycobiome at the species level. Many fungal microorganisms were significantly higher in the EES group when compared to the controls. Confirmation of these results in larger trials will provide further evidence regarding the impact of EES on gut microbiota when utilized as a prokinetic agent.